A comparison of long-term healthcare utilization and costs in patients with acute severe ulcerative colitis receiving infliximab versus early colectomy. (January 2019) - Vasudevan, Abhinav; Arachchi, Asiri; Scanlon, Cian; Greenhalgh, Jarrod; Van Langenberg, Daniel R.
Background: Early intervention for acute severe ulcerative colitis (ASUC) improves outcomes. Outcomes and healthcare costs for an infliximab-first and colectomy-first approach were compared. Methods: This single-center retrospective cohort study of inpatients with steroid-refractory ASUC who received infliximab 5 mg/kg (1–3 doses without maintenance) or initial colectomy between 2004 and 2014 assessed long-term healthcare utilization and direct costs following infliximab or colectomy, using admission coding data until 31 December 2016. Results: A total of 118 patients received either infliximab ( n = 85, 72%) or colectomy ( n = 33, 28%) as initial therapy, with 35(41%) patients eventually requiring colectomy post-infliximab (median 213 days, range [6, 3739]). Median follow up was 7 years [0, 14]. Following infliximab for ASUC, 44% of patients then received antitumor necrosis factor maintenance. After ASUC therapy, length of stay and number of admissions did not significantly differ between groups but higher numbers of complications prompting readmission occurred in the colectomy group (median 4 versus 1, p < 0.001). There were no differences in admissions or total length of stay for patients who had received infliximab first then colectomy versus those treated with colectomy first (median 7.0 versus 4.0, 41.5 days versus 29 days, respectively, each p > 0.05). Total costs were lower at 6 months (mean AUD17, 662 versus AUD24, 852, p = 0.003), yet were similar at 7 years following an infliximab compared with colectomy approach (AUD72, 834 versus AUD59, 557, p = 0.23). After infliximab, costs were significantly higher at 7 years with biologic rather than immunomodulator-only maintenance therapy (AUD109, 365 versus AUD47, 842, p < 0.01). Conclusions: In support of current practice, infliximab salvage in steroid-refractory ASUC achieved reduced short-term healthcare costs compared with initial colectomy, though long-term costs were not significantly different.